The influence of quail bird fertilizer on the growth and results of plant growth in alluvial soil - Budiman, Maulidi, Mulyadi Safwan, Ahmad (Jurnal Sains Pertanian Equator, 2019)
This study aims to determine the best dose of quail manure to increase growth and yield of squash on alluvial soil. This research was carried out in the experimental garden of the Tanjungpura University Faculty of Agriculture, Ahmad Yani Street starting in December 2017 until March 2018. The design used was a completely randomized design (CRD) consisting of six treatments, four replications and three sample plants. The treatment given was k1 = 150g / polybag, k2 = 300g / polybag, k3 = 450g / polybag, k4 = 600g / polybag, k5 = 750g / polybag, and k6 = 900g / polybag. Variable effects in this study were the amount of leaf chlorophyll, root volume, plant dry weight, fruit weight, fruit length, frit diameter and number of fruit plant. The reslt of the study showed that luffa plants give a different response towards giving quail manure fertilizer to the variables amount of leaf chlorophyll, root volume, plant dry weight and give a different response to frui weight, fruit length, fruit diameter and number of fruit crops on variable amounts of leaf chlorophyll, root volume, plant dry weight, fruit length and number of fruit diameter, and gave different responses to fruit weight, fruit length and number of fruit plantations. The results showed that 750 g quail manure diosage gave the highest average for growth and yield compared to other doses.Keywods: alluvial, quail manure, squash.